Oral swabs as a proxy for direct ruminal microbiome sampling in Holstein dairy cows is correlated with sample color - Skarlupka, Joseph H.; Cox, Madison S.; Steinberger, Andrew J.; Sbardellati, Dino L.; McClure, Jennifer C.; Bickhart, Derek M.; Scheftgen, Andrew J.; Zuniga-Chaves, Ibrahim; Wolfe, Luke A.; Paget, Eric; Skadron, Charles; Attipetty, Nithya; et al. (Frontiers in Microbiology, 2024)
Using oral swabs to collect the remnants of stomach content regurgitation during rumination in dairy cows can replicate up to 70% of the ruminal bacterial community, offering potential for broad-scale population-based studies on the rumen microbiome. The swabs collected from dairy cows often vary widely with respect to sample quality, likely due to several factors such as time of sample collection and cow rumination behavior, which may limit the ability of a given swab to accurately represent the ruminal microbiome. One such factor is the color of the swab, which can vary significantly across different cows. Here, we hypothesize that darker-colored swabs contain more rumen contents, thereby better representing the ruminal bacterial community than lighter-colored swabs. To address this, we collected oral swabs from 402 dairy cows and rumen samples from 13 cannulated cows on a research farm in Wisconsin, USA and subjected them to 16S rRNA sequencing. In addition, given that little is known about the ability of oral swabs to recapitulate the ruminal fungal community, we also conducted ITS sequencing of these samples. To correlate swab color to the microbiota we developed and utilized a novel imaging approach to colorimetrically quantify each swab from a range of light to dark. We found that swabs with increasing darkness scores were significantly associated with increased bacterial alpha diversity (p < 0.05). Lighter swabs exhibited greater variation in their community structure, with many identified amplicon sequence variants (ASVs) categorized as belonging to known bovine oral and environmental taxa. Our analysis of the fungal microbiome found that swabs with increasing darkness scores were associated with decreased alpha diversity (p < 0.05) and were also significantly associated with the ruminal solids fungal community, but not with the ruminal liquid community. Our study refines the utility of oral swabs as a useful proxy for